FREQUENCY OF ANXIETY AND DEPRESSION IN CHRONIC HEPATITIS C PATIENTS VISITING A TERTIARY CARE HOSPITAL AT GADAP TOWN, KARACHI - Bhutto, Abdul Rabb; Jatt, Muhammad Ilyas; Rafi, Shumaila; Washdev, Washdev; Arsalan, Muhammad; Ullah, Aman (Journal of Postgraduate Medical Institute, 2019)
Objective: To determine the frequency of anxiety and depression in chronic hepatitis C patients. Methodology: In this cross sectional study conducted at a private medical college hospital, adult subjects of either sex with positive antibodies to hepatitis C of more than 6 months' duration were enrolled after taking informed consent. After implementation of inclusion and exclusion criteria subjects were interviewed for the presence and severity of anxiety and depression by Beck anxiety inventory and Beck depression inventory questionnaires respectively. Results: The mean age of 264 naí¯ve hepatitis C subjects was 39.826 ±10.6121 (ranging from 17 to 71) years. Among those, 127 (48.1%) were males while 137 (51.9%) were female. Mean duration of hepatitis C was 3.665 ±2.445 (range 0.1 to 12) years. Anxiety was found in 177 (67%) subjects and males had higher frequency as compared to females (70.9% versus 63.5%). Depression was found in 191 (72.3%) subjects, In contrast to anxiety, depression was more prevalent in females 106 (77.4%) as compared to males 85 (66.9%). Conclusion: Anxiety and depression were found in a significantly high number of naí¯ve hepatitis C patients.